Chemical composition and antimicrobial activity of essential oils of Prangos trifida s.l. - Ušjak, Ljuboš; Stojković, Dejan; Soković, Marina; Niketić, Marjan; Petrović, Silvana (Archives of Pharmacy, 2022)
In this study composition and antimicrobial activity of essential oils of roots, leaves, stems and fruits of Prangos trifida (Mill.) Herrnst. & Heyn s.l. (Apiaceae) were investigated. Plant material was collected in ​​Sićevo Gorge (Kusača) in 2020. Essential oils were isolated by hydrodistillation in Clevenger-type apparatus and analyzed by GC-FID-MS. Antimicrobial activity was tested by microdilution method against food contaminants: Gram-positive (Staphylococcus aureus, Bacillus cereus and Listeria monocytogenes), Gram-negative bacteria (Escherichia coli, Enterobacter cloacae and Salmonella Typhimurium), and molds (Aspergillus fumigatus, A. niger, A. versicolor, Penicillium funiculosum, P. verrucosum var. cyclopium and Trichoderma harzianum); artificial food preservatives E211 and E224 were used as controls. Dominant constituents of essential oils were monoterpenes (66.2-87.2%). Terpinolene (36.2%) and p-cymene (11.5%) prevailed in root oil, (E)-β-ocimen (23.2%) and terpinolene (18.1%) in leaf oil, p-cimen-8-ol (21.8%) and p-cimen (14.1%) in stem oil, and p-cimen (25.4%) and limonene (14.4%) in fruit oil. Essential oils showed significant antifungal activity (MIC=0.10-0.78 mg/mL; MFC=0.20-1.56 mg/mL), better compared to both tested commercial preservatives, and interesting antibacterial activity (MIC=0.20-6.25 mg/mL; MBC=0.39-12.5 mg/mL), which was in the case of root and stem oils better than activity of both preservatives against S. aureus and B. cereus. It should be noted that composition of tested oils was in accordance with composition of the oils of this plant from vicinity of ​​Madrid and from Crimea, while their antimicrobial activity was tested in this work for the first time. Obtained results justify further research of P. trifida essential oils as new natural food preservatives.